Laminate, decorative sheet, and heat or active energy ray curable coating agent
The laminate with a resin layer containing specific resin beads or silica addresses the inconsistency in tactile sensation of existing decorative sheets by controlling friction, roughness, and hardness, resulting in a consistent and smooth touch experience.
Patent Information
- Application Number
- JP2023175079
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-10
- Publication Date
- 2025-04-22
AI Technical Summary
Existing decorative sheets with characteristic textures struggle to provide a consistent and smooth tactile sensation due to variations in user evaluations, which are influenced by physical condition and sensation.
A laminate with a resin layer formed from a heat or active energy ray curing composition containing 1 to 50% by mass of resin beads or silica, with specific dynamic friction, roughness, and Young's modulus values to achieve a smooth tactile sensation.
The laminate achieves a consistent and smooth tactile sensation, reducing variations in user evaluations by controlling the dynamic friction coefficient, surface roughness, and resin bead hardness within specific ranges.
Smart Images

Figure 2025065695000001 
Figure 2025065695000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate having a characteristic feel, a decorative sheet, and a heat or active energy ray curable coating agent used therefor. [Background technology]
[0002] In recent years, interest in sensory value, which adds new value to products, has increased, and many industries are actively working to create sensory value. The pleasant feel of a product, which is perceived as a touch sensation, is attracting attention as an important factor in adding value to a product. One of the applications that require a good tactile feel is a decorative sheet used for interior building materials. As decorative sheets with a characteristic tactile feel, in addition to wood grain decorative sheets that are given a tactile feel similar to that of real wood grain, decorative sheets having a surface resin layer containing a polymer-based lubricant and an organic particle-based lubricant for the purpose of a smooth tactile feel (see, for example, Patent Document 1), decorative sheets that include a thermoplastic resin layer, have an uneven pattern on the surface, and have an arithmetic mean roughness Ra of the surface of the uneven pattern of 15 μm or more and 25 μm or less, and an average length RSm of the contour curve elements of 400 μm or less, where Ra is the arithmetic mean height according to JIS B0601:2001, and RSm is the average length of the elements (see, for example, Patent Document 2), are known. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2023-10419 A [Patent Document 2] Patent Publication No. 2021-53996 Summary of the Invention [Problem to be solved by the invention]
[0004] The problem to be solved by the present invention is to provide a decorative sheet that can be applied to decorative sheets and has a distinctive feel, and a heat or active energy ray curable coating agent for use therewith. [Means for solving the problem]
[0005] The "smooth texture" described in References 1 and 2 is evaluated as "particularly smooth, like wood that has been treated with a soap finish" in Reference 1, which is rated A (see paragraph 0110 of Reference 1), and as "more than 18 people answered that the texture was smooth" in Reference 2, which is rated ○ (see paragraph 0031 of Reference 2). Both are judged by sensory evaluation. Although sensory evaluation is a useful evaluation because it is the average of the evaluations of people who actually use the product, the evaluation values can vary widely depending on the physical condition and sense of the test subject. Furthermore, there are various ways to describe the texture, such as "moist," "soft," "smooth," and "silky," in addition to "smooth," but it is unclear whether each test subject uses these with a unified recognition, and there is still the problem of large variation.
[0006] As a result of extensive research to solve the above-mentioned problems, the inventors have discovered that tactile sensation can be specified by the dynamic friction coefficient obtained by measurement with a human hand, the average roughness Ra, which is a value representing the unevenness of a surface, and the Young's modulus, which is a value representing the hardness of the resin beads in the laminate, and that a laminate having a resin layer of a heat or active energy ray curable composition containing a specific amount of resin beads having a specific particle size can express a "smooth" tactile sensation, thereby solving the above-mentioned problems.
[0007] That is, the present invention provides a laminate having a substrate and a resin layer provided on the substrate, the resin layer satisfying (1) to (4). (1) The resin layer is a layer formed by applying heat or active energy ray curing to the resin layer, the resin layer being a heat or active energy ray curing composition containing 1 to 50 mass % of 1 to 10 μm resin beads or 1 to 50 mass % of silica, to form a film. (2) The coefficient of kinetic friction of the resin layer surface is 0.35 or less. (3) The average roughness Ra, which represents the unevenness of the surface, is 3 μm or less, and the maximum height Rz is 20 μm or less. (4) The Young's modulus, which is the hardness value of the resin beads in the laminate, is 1000 MPa or more.
[0008] The present invention also provides a laminate, wherein the resin layer is a layer formed by thermally coating a resin layer of a thermosetting composition containing a polyol and an isocyanate, the resin layer containing 1 to 50% by mass of resin beads having an average particle size of 1 to 10 μm or 1 to 50% by mass of silica.
[0009] The present invention also provides a laminate, wherein the resin layer is a layer formed by irradiating an active energy ray with a resin layer of an active energy ray-curable composition containing a (meth)acrylic monomer containing 1 to 50 mass % of resin beads having an average particle size of 1 to 10 μm or 1 to 50 mass % of silica.
[0010] The present invention also provides a heat- or active energy ray-curable coating agent containing 1 to 50 mass % of resin beads having an average particle size of 1 to 10 μm or 1 to 50 mass % of silica, wherein a layer formed by irradiation with heat or active energy rays satisfies (2) to (4). (2) The coefficient of kinetic friction of the resin layer surface is 0.35 or less. (3) The average height Ra, which is a value representing the unevenness of the surface, is 3 μm or less, and the maximum height Rz is 20 μm or less. (4) The Young's modulus, which is the hardness value of the resin beads in the laminate, is 1000 MPa or more.
[0011] The present invention also provides a decorative sheet using the laminate. Effect of the Invention
[0012] The laminate of the present invention can provide a decorative sheet that is applicable to decorative sheets and has a distinctive feel to the touch, and a heat or active energy ray curable coating agent for use therewith. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] (Laminate) The laminate of the present invention is a laminate having a substrate and a resin layer provided on the substrate, characterized in that the resin layer satisfies (1) to (4). (1) The resin layer is a layer formed by applying heat or active energy ray curing to the resin layer, the resin layer being a film-formed resin layer of a heat or active energy ray curing composition containing 1 to 50 mass % of resin beads having an average particle size of 1 to 10 μm or 1 to 50 mass % of silica. (2) The coefficient of kinetic friction of the resin layer surface is 0.35 or less. (3) The average height Ra, which is a value representing the unevenness of the surface, is 3 μm or less, and the maximum height Rz is 20 μm or less. (4) The Young's modulus, which is the hardness value of the resin beads in the laminate, is 1000 MPa or more.
[0014] (base material) The substrate used in the present invention is not particularly limited, and a substrate according to the desired purpose can be appropriately used. For example, a film or sheet-like substrate made of a polyolefin resin such as polyethylene (LLDPE: low density polyethylene, HDPE: high density polyethylene, MDOPE: uniaxially oriented polyethylene, OPE: biaxially oriented polyethylene), polypropylene (CPP: non-oriented polypropylene film, OPP: biaxially oriented polypropylene film), polybutene, polymethylpentene, ethylene-propylene copolymer, ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, ethylene-propylene-butene copolymer, or polyolefin thermoplastic elastomer can be mentioned. Other examples include film or sheet-like substrates made of polyethylene terephthalate (PET), polystyrene, polyamide, polyacrylonitrile, ethylene-vinyl alcohol copolymer, polyvinyl alcohol, ethylene-vinyl alcohol copolymer, and the like. Furthermore, these substrates may be single-layered or may be multi-layered.
[0015] To form a film or sheet-like substrate, for example, a molding method such as a calendar method, an inflation method, a T-die extrusion method, etc. The thickness of these is not particularly limited and can be set according to the product characteristics, but is usually about 40 to 150 μm, preferably about 50 to 100 μm.
[0016] The base material may contain additives as necessary. Examples of additives include fillers such as calcium carbonate and clay, flame retardants such as magnesium hydroxide, antioxidants, lubricants, foaming agents, colorants, etc. The amount of additives to be added can be appropriately determined depending on the product characteristics.
[0017] One or both sides of the substrate may be subjected to a surface treatment such as corona discharge treatment, ozone treatment, plasma treatment, ionizing radiation treatment, dichromate treatment, etc. For example, when corona discharge treatment is performed, the surface tension of the substrate surface may be set to 30 dyne or more, preferably 40 dyne or more. The surface treatment may be performed according to a conventional method for each treatment.
[0018] In addition, substrates such as paper, wood, and leather can be used without any problem. For example, as the paper, any known paper substrate can be used without any particular limitation, and specifically, the paper is manufactured by a known paper machine using natural fibers for papermaking such as wood pulp. Examples of natural fibers for papermaking include wood pulp such as softwood pulp and hardwood pulp, non-wood pulp such as Manila hemp pulp, sisal hemp pulp, and flax pulp, and pulps obtained by chemically modifying these pulps. As the type of pulp, chemical pulp by sulfate cooking method, acidic / neutral / alkaline sulfite cooking method, soda salt cooking method, ground pulp, chemi-ground pulp, thermomechanical pulp, etc. can be used. In addition, various commercially available wood-free papers, coated papers, backing papers, impregnated papers, cardboard, paperboard, etc. can also be used.
[0019] (Resin layer) In the present invention, the resin layer is characterized by satisfying the following requirements (1) to (4). (1) The resin layer is a layer formed by applying heat or active energy ray curing to the resin layer, the resin layer being a heat or active energy ray curing composition containing 1 to 50 mass % of 1 to 10 μm resin beads or 1 to 50 mass % of silica, to form a film. (2) The coefficient of kinetic friction of the resin layer surface is 0.35 or less. (3) The average roughness Ra, which represents the unevenness of the surface, is 3 μm or less, and the maximum height Rz is 20 μm or less. (4) The Young's modulus, which is the hardness value of the resin beads in the laminate, is 1000 MPa or more.
[0020] (Resin beads) The resin beads having an average particle size of 1 to 10 μm used in the resin layer (1) of the present invention are not particularly limited, and examples of the material that can be suitably used include organic polymer components (or resin components) such as urethane resins, melamine resins, polyamide resins, amino resins, (meth)acrylic resins, polyethylene resins, polystyrene resins, polypropylene resins, polyester resins, cellulose resins, vinyl chloride resins, polyvinyl alcohol, ethylene-vinyl acetate copolymers, ethylene-vinyl alcohol copolymers, ethylene-ethyl acrylate copolymers, polyacrylonitrile, and polyamides.
[0021] Among these, (meth)acrylic resin beads are preferred. Examples of acrylic esters, which are raw materials for (meth)acrylic resins, include methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, hexyl acrylate, octyl acrylate, hydroxyethyl acrylate, 2-ethylhexyl acrylate, and glycidyl acrylate. Examples of methacrylic acid esters that are raw materials for (meth)acrylic resins include methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, hexyl methacrylate, octyl methacrylate, hydroxyethyl methacrylate, 2-ethylhexyl methacrylate, and glycidyl methacrylate. Among these, in the present invention, (meth)acrylic resin beads made from butyl methacrylate are preferred because they provide a smooth feel to the touch.
[0022] (silica) The silica having an average particle size of 1 to 10 μm used in the resin layer (1) of the present invention is not particularly limited, and for example, dry silica, wet silica, etc. can be used. In addition, any silica can be used regardless of its oil absorption amount or shape.
[0023] In the present invention, the average particle size of the resin beads or silica is calculated from the state of frequency distribution measured using a scanning electron microscope S-3400N manufactured by Hitachi, Ltd. as an average particle size measuring method.
[0024] The resin beads and the silica are contained in an amount of 1 to 50% by mass relative to the solid content of the heat- or active energy ray-curable composition described below. Of these, the amount is preferably 1 to 45% by mass, and most preferably 1 to 25% by mass. The resin beads and the silica may be used alone or in combination of two or more types. Even when used in combination, the amount is preferably 1 to 50% by mass relative to the solid content of the heat- or active energy ray-curable composition described below. Of these, the amount is preferably 1 to 45% by mass, and most preferably 1 to 25% by mass.
[0025] (Thermosetting composition) The thermosetting composition used in the (1) resin layer of the present invention may be, for example, a composition using an isocyanate compound or an epoxy compound as a thermosetting agent and a polymeric compound having an active hydrogen group, which has a group capable of reacting with an isocyanate group or an epoxy group and can serve as a binder resin. As the polymeric compound having an active hydrogen group, a polymeric compound having two or more types of functional groups in one molecule is preferred because it can form a three-dimensional crosslinked structure after curing, and an acrylic resin, a polyester resin, a urethane resin, or the like having two or more types of functional groups selected from a hydroxyl group, an amino group, and a carboxyl group in one molecule is preferred. When the thermosetting composition is used as a decorative sheet, an example of a particularly preferred embodiment is an acrylic resin having two or more hydroxyl groups in one molecule.
[0026] As the heat curing agent, an isocyanate compound is preferred, and a polyisocyanate compound having two or more isocyanate groups in one molecule is preferred because it can form a three-dimensional crosslinked structure after curing. Examples of polyisocyanate compounds having two or more isocyanate groups in one molecule that react with the functional group of the thermosetting resin composition include tolylene diisocyanate (TDI), 4,4'-diphenylmethane diisocyanate (MDI), xylylene diisocyanate (XDI) and hydrogenated compounds thereof, isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI) and other compounds having two isocyanate groups in one molecule, and polyisocyanates having three or more isocyanate groups in one molecule synthesized by a known technique from one or more compounds selected from these. Also, a composition in which one or more types selected from these different types of polyisocyanates are mixed can be used.
[0027] Preferred are trimer type, TMP adduct type and biuret type synthesized by a known technique from one or more compounds selected from TDI, XDI, IPDI and HDI.
[0028] The content of the isocyanate compound relative to the resin component can be set arbitrarily, but generally, the equivalent ratio of hydroxyl group / isocyanate is often 1 / 0.5 to 1 / 3.
[0029] (Organic solvent) The thermosetting composition may contain an organic solvent as a diluent, for example, aromatic hydrocarbons such as toluene and xylene, aliphatic or alicyclic hydrocarbons such as n-hexane and cyclohexane, esters such as ethyl acetate, butyl acetate, and propyl acetate, alcohols such as methanol, ethanol, and isopropyl alcohol, ketones such as acetone and methyl ethyl ketone, and alkylene glycol monoalkyl ethers such as ethylene glycol monoethyl ether and propylene glycol monomethyl ether.
[0030] (Additives) The thermosetting composition may contain various additives, such as inorganic pigments, organic pigments, extender pigments, clay minerals, waxes, surfactants, stabilizers, flow adjusters, dyes, leveling agents, rheology control agents, ultraviolet absorbers, antioxidants, and plasticizers, as necessary.
[0031] The method of forming a resin layer using the thermosetting composition is not particularly limited, and a resin layer is formed on the substrate by a known coating / printing method. Specific examples of the coating / printing method include a roll coater, gravure coater, flexo coater, air doctor coater, blade coater, air knife coater, squeeze coater, impregnation coater, transfer roll coater, kiss coater, curtain coater, cast coater, spray coater, die coater, offset printing machine, screen printing machine, etc., which can be appropriately used as a coating method.
[0032] The thickness of the resin layer formed using the thermosetting composition is not particularly limited, but is preferably 1 to 30 μm, more preferably 1 to 25 μm, and particularly preferably 1 to 20 μm. As long as the thickness is within the above range, the effects of the present application can be obtained.
[0033] The method for curing the thermosetting composition used in the present invention is not particularly limited, and the composition can be cured by any known heating method.
[0034] (Active energy ray-curable composition) The active energy ray-curable composition used in the resin layer (1) of the present invention may, for example, be a composition containing a compound having a (meth)acryloyl group and, if necessary, a photopolymerization initiator.
[0035] (Compound having a (meth)acryloyl group) Examples of compounds having a (meth)acryloyl group include monofunctional (meth)acrylates such as ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, hexadecyl (meth)acrylate, octadecyl (meth)acrylate, isoamyl (meth)acrylate, isodecyl (meth)acrylate, isostearyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, methoxyethyl (meth)acrylate, butoxyethyl (meth)acrylate, phenoxyethyl (meth)acrylate, and phenoxydiethylene glycol. (meth)acrylate, nonylphenoxyethyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, glycidyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 3-chloro-2-hydroxypropyl (meth)acrylate, diethylaminoethyl (meth)acrylate, nonylphenoxyethyl tetrahydrofurfuryl (meth)acrylate, caprolactone-modified tetrahydrofurfuryl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, ethoxyethoxyethanol acrylic acid polymer ester, and the like.
[0036] Examples of bifunctional (meth)acrylates include 1,4-butanediol di(meth)acrylate, 3-methyl-1,5-pentanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 2-methyl-1,8-octanediol di(meth)acrylate, 2-butyl-2-ethyl-1,3-propanediol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, dipropionyl ... Examples of the di(meth)acrylate include dihydric alcohol di(meth)acrylates such as ethylene glycol di(meth)acrylate and tripropylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, di(meth)acrylate of tris(2-hydroxyethyl)isocyanurate, di(meth)acrylates of diols obtained by adding 4 or more moles of ethylene oxide or propylene oxide to 1 mole of neopentyl glycol, and di(meth)acrylates of diols obtained by adding 2 moles of ethylene oxide or propylene oxide to 1 mole of bisphenol A.
[0037] Examples of the trifunctional or higher (meth)acrylate include poly(meth)acrylates of trihydric or higher polyhydric alcohols such as trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, and dipentaerythritol poly(meth)acrylate; poly(meth)acrylates of polyoxyalkylene polyols such as triol tri(meth)acrylates obtained by adding 3 moles or more of ethylene oxide or propylene oxide to 1 mole of glycerin, triol di- or tri(meth)acrylates obtained by adding 3 moles or more of ethylene oxide or propylene oxide to 1 mole of trimethylolpropane, and di(meth)acrylates of diols obtained by adding 4 moles or more of ethylene oxide or propylene oxide to 1 mole of bisphenol A.
[0038] Furthermore, a mixture of dipentaerythritol hexaacrylate and dipentaerythritol pentaacrylate (sometimes abbreviated as DPHA), which are bifunctional or higher (meth)acrylates, ditrimethylolpropane tetraacrylate (sometimes abbreviated as DTMPTA), trimethylolpropane ethylene oxide adduct tri(meth)acrylate, which is a triol tri(meth)acrylate obtained by adding 3 moles or more of ethylene oxide to 1 mole of trimethylolpropane, etc. may be used. A representative example of the trimethylolpropane ethylene oxide adduct tri(meth)acrylate is trimethylolpropane ethylene oxide (hereinafter, ethylene oxide may be referred to as "EO") modified (n≒3) triacrylate.
[0039] Furthermore, a polymerizable oligomer or a polymerizable polymer may be used as necessary. Examples of the polymerizable oligomer include urethane (meth)acrylate, amine-modified polyether acrylate, amine-modified epoxy acrylate, amine-modified aliphatic acrylate, amine-modified polyester acrylate, amine-modified acrylate such as amino (meth)acrylate, polyester (meth)acrylate, polyether (meth)acrylate, polyolefin (meth)acrylate, polystyrene (meth)acrylate, etc. Examples of the polymerizable polymer include acrylic resins containing a (meth)acryloyl group, etc.
[0040] (Photopolymerization initiator) When ultraviolet rays or the like are used as the active energy rays, a photopolymerization initiator is used. There are no particular limitations on the photopolymerization initiator, and any known radical polymerization type photopolymerization initiator can be used. Examples of the photopolymerization initiator include α-hydroxyalkyl ketone-based photopolymerization initiators such as 1-phenyl-2-hydroxy-2-methylpropan-1-one, 1-(4-i-propylphenyl)-2-hydroxy-2-methylpropan-1-one, 4-(2-hydroxyethoxy)phenyl-(2-hydroxy-2-propyl)ketone, and 1-hydroxycyclohexylphenyl ketone, phenylglyoxolate-based photopolymerization initiators such as methylbenzoyl formate, and monoacylphosphine oxides such as 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 2,6-dimethoxybenzoyl-diphenylphosphine oxide, 2,6-dichlorobenzoyl-diphenylphosphine oxide, 2,4,6-trimethylbenzoyl-phenylphosphinic acid methyl ester, 2-methylbenzoyl-diphenylphosphine oxide, and pivaloylphenylphosphinic acid isopropyl ester. These photopolymerization initiators may be used alone or in combination of two or more. The total amount of the photopolymerization initiators is often within the range of 0.1 to 20% by mass based on the total amount of the coating agent. In addition, a tertiary amine compound selected from an aliphatic amine derivative and / or a benzoic acid amine derivative may be used in combination as a sensitizer.
[0041] (Additives) The active energy ray-curable composition may contain various additives, such as inorganic pigments, organic pigments, extender pigments, clay minerals, waxes, surfactants, stabilizers, flow adjusters, dyes, leveling agents, rheology control agents, ultraviolet absorbers, antioxidants, or plasticizers, as necessary.
[0042] The method of forming a resin layer using the active energy ray curable composition is not particularly limited, and a resin layer is formed on the substrate by a known coating / printing method. Specific examples of the coating / printing method include a roll coater, gravure coater, flexo coater, air doctor coater, blade coater, air knife coater, squeeze coater, impregnation coater, transfer roll coater, kiss coater, curtain coater, cast coater, spray coater, die coater, offset printing machine, screen printing machine, etc., which can be appropriately used as a coating method.
[0043] (Curing method) When the active energy ray-curable composition is cured by ultraviolet irradiation, the ultraviolet light source may be, for example, a germicidal lamp, an ultraviolet fluorescent lamp, an ultraviolet light-emitting diode (UV-LED), a carbon arc, a metal halide lamp, a xenon lamp, a chemical lamp, a low-pressure mercury lamp, a high-pressure mercury lamp for copying, a medium-pressure or high-pressure mercury lamp, an ultra-high-pressure mercury lamp, an electrodeless lamp, a metal halide lamp, natural light, etc. The integrated light quantity of the ultraviolet light is not particularly limited, but is preferably 20 to 3000 mJ / cm. 2 The range is preferably 20 to 1000 mJ / cm 2 The range is more preferable.
[0044] When the active energy ray-curable composition is cured by electron beam irradiation, various electron beam accelerators such as Cockcroft-Walton type, Van de Graaff type, resonant transformer type, insulating core transformer type, linear type, dynamitron type, high frequency type, etc. are used. The irradiation dose is not particularly limited, but is preferably about 10 to 230 kGy, more preferably about 10 to 100 kGy.
[0045] The thickness of the resin layer formed by using the active energy ray-curable composition is not particularly limited, but is preferably 1 to 30 μm, more preferably 1 to 25 μm, and particularly preferably 1 to 20 μm. If the thickness is within the above range, the effects of the present application can be obtained.
[0046] (Kinematic friction coefficient of hand on resin layer surface) The resin layer used in the present invention has (2) a coefficient of dynamic friction of the hand on the resin layer surface of 0.35 or less. The coefficient of dynamic friction of the hand on the resin layer surface is a value measured by the following method.
[0047] Using a tribometer (Tactile Force Plate TF-2020, sold by Tech Gihansha), the coating film was placed on the tribometer, and the palm of the right hand was used to trace the surface of the resin layer while changing the speed and vertical load. The dynamic friction coefficient was measured for 30 seconds. During the 30-second measurement, the dynamic friction coefficients at a vertical load of 200g and a speed of 50mm / s were collected and averaged. The same experiment was also conducted on three men and three women in their 20s to 50s, and the dynamic friction coefficients of a total of six people were averaged to obtain the value.
[0048] In the present invention, the dynamic friction coefficient is 0.35 or less, and more preferably 0.1 to 0.30. If it is less than 0.10, no frictional resistance is felt, resulting in discomfort.
[0049] (Average roughness Ra, maximum height Rz) The resin layer used in the present invention has (3) an average roughness Ra, which is a value representing the unevenness of the surface, of 3 μm or less and a maximum height Rz of 20 μm or less. Here, the average roughness Ra and the maximum height Rz are values measured by the following method.
[0050] The resin layer surface is scanned at a scanning speed of 0.06 mm / s using a contact type roughness meter (Tokyo Seimitsu Co., Ltd., SURFCOM NEX) with a spherical indenter with a tip radius of 2 μm, and the average roughness Ra and maximum height Rz are obtained from a roughness curve using a reference length and low-pass cutoff length in accordance with JIS B0601 and JIS B0633.
[0051] In the present invention, the average roughness Ra is 3 μm or less, preferably 1.6 μm or less, and most preferably 1.2 μm or less, while the lower limit is preferably 0.1 μm, more preferably 0.2 μm or more, and most preferably 0.4 μm or more.
[0052] In the present invention, the maximum height Rz is 20 μm or less, preferably 12 μm or less, and most preferably 10 μm or less, while the lower limit is preferably 1 μm, more preferably 2 μm or more, and most preferably 4 μm or more.
[0053] (Young's Modulus) The resin layer used in the present invention has (4) a Young's modulus, which is the value of the hardness of the resin beads in the laminate, of 1000 MPa or more. Here, the Young's modulus is a value measured by the following method.
[0054] Using a nanoindenter (Elionix, ENT-2100), measurements were taken at the center of the bead observed in the microscopic image of the resin layer surface using a Berkovich indenter with an indentation load of 25 μN, an indentation time of 10 seconds, a creep time of 10 seconds, and an unloading time of 10 seconds. The Young's modulus of the bead was obtained from the unloading portion of the obtained load-displacement curve using the Oliver-Pharr method in accordance with ISO14577.
[0055] In the present invention, the Young's modulus is 1000 MPa or more, preferably 1000 MPa or more, and more preferably 2000 MPa or more.
[0056] (decorative sheet) The decorative sheet using the laminate of the present invention may be a decorative sheet having a substrate and a resin layer provided on the substrate as described above, or may have known layers on the substrate that are usually provided on decorative sheets, such as a pattern layer, a primer layer, etc. The resin layer used in the present invention is a layer that provides a tactile sensation, and is therefore located on the outermost surface of the decorative sheet.
[0057] (Picture layer) The substrate used in the present invention may have a pattern layer. The pattern layer is usually provided by printing. The pattern layer may be a single layer, or multiple layers may be laminated. Furthermore, the pattern layer may be solid printing, or may be a pattern layer printed only on a part of the substrate. A printed pattern layer may also be called a printed layer. The design layer can be printed on the substrate by a known coating or printing method, such as roll coating, gravure coating, spray coating, or gravure printing, offset printing, letterpress printing, screen printing, or inkjet printing. The pattern to be applied to the design layer may be freely determined, and examples thereof include a wood grain pattern, a pattern imitating the surface of a rock such as a marble pattern, a fabric pattern imitating the grain of a fabric or a pattern on a fabric, a tile pattern, a floral pattern in which flowers or bunches of flowers are arranged at equal intervals, letters, etc. In order to make the pattern stand out, a solid printed layer such as a white background may be provided under the pattern printed layer.
[0058] The ink constituting the design layer may be any known ink, such as an oil-based ink, a water-based ink, an active energy ray curable ink, etc. In addition, a liquid printing ink such as a flexographic printing ink or a gravure printing ink, a lithographic offset printing ink, an inkjet ink, etc. may be selected according to the printing method.
[0059] (Primer layer) The primer layer provided to improve the adhesion between the substrate, the design layer, and the resin layer is not particularly limited, and any known primer layer can be provided. An example of the primer layer is a layer formed by coating a solution of, for example, vinyl chloride-vinyl acetate copolymer, acrylic resin, polyester resin, polyurethane resin (two-component curing type consisting of an isocyanate curing agent and various polyols), chlorinated polypropylene, chlorinated polyethylene, etc. In addition to the above resins, additives such as fillers such as silica fine powder, light stabilizers, etc. may be added. The primer layer can be formed by coating these compositions and drying and curing them as necessary.
[0060] (Decorative materials) A decorative material can be obtained by laminating the decorative sheet of the present invention to wood, plywood, fiberboard, metal plate, etc. The decorative sheet of the present invention can also be used for residential interior materials, furniture, home appliances, office supplies, toys, vehicle interior materials, etc., which require antibacterial properties, and is particularly suitable for use in residential interior materials, furniture, and home appliances. EXAMPLES
[0061] The present invention will now be described in more detail with reference to examples. In the following, all "parts" and "%" are based on mass.
[0062] In the present invention, the number average molecular weight and weight average molecular weight (converted into polystyrene) were measured by GPC using an HLC8220 system manufactured by Tosoh Corporation under the following conditions. Separation columns: four TSKgel GMHHR-N columns manufactured by Tosoh Corporation. Column temperature: 40°C. Mobile phase: tetrahydrofuran manufactured by Wako Pure Chemical Industries, Ltd. Flow rate: 1.0 ml / min. Sample concentration: 1.0 wt%. Sample injection amount: 100 microliters. Detector: differential refractometer. The average particle size of the resin beads was calculated from the frequency distribution measured using a scanning electron microscope S-3400N manufactured by Hitachi, Ltd. as an average particle size measurement method.
[0063] (Adjustment method) (Adjustment example 1 thermosetting composition) 28 parts by mass of an acrylic polyol resin with a glass transition temperature (Tg) of 50°C and 10 parts by mass of acrylic beads "GB-05S" made from butyl methacrylate manufactured by Negami Chemical Industries Co., Ltd. were mixed and diluted with ethyl acetate, and stirred for about 1 hour with a stirrer. Just before coating, 15 parts by mass of isocyanate "Desmodur N-3300" manufactured by Covestro was added as a heat curing agent, and the mixture was thoroughly stirred to obtain a thermosetting composition of Preparation Example 1. Thermosetting compositions of Preparation Examples 1 to 3 and Comparative Preparation Examples 1 to 4 were obtained in the same manner as Preparation Example 2, except that the composition raw materials and ratios were changed as shown in Tables 1 and 2.
[0064] (Preparation Example 4: Active Energy Ray-Curable Composition) 85 parts by mass of a trifunctional acrylate monomer "Miramer M3130" manufactured by MIWON, 5 parts by mass of 1-hydroxy-cyclohexyl-phenyl-ketone "Omnirad 184" manufactured by IGM Resins BV as a photopolymerization initiator, and 10 parts by mass of acrylic beads "GB-05S" made from butyl methacrylate manufactured by Negami Chemical Industries, Ltd. were mixed and stirred with a stirrer for about 1 hour to prepare an active energy ray-curable composition of Preparation Example 4. An active energy ray-curable composition of Preparation Example 5 was obtained in the same manner as Preparation Example 4, except that the composition raw materials and ratios were changed as shown in Tables 1 and 2. The abbreviations in Tables 1 and 2 are as follows. The unit of particle size is μm.
[0065] Thermosetting resin: Acrylic polyol resin Photocurable resin: MIWON's trifunctional acrylate monomer Miramer M3130 Photoinitiator: 1-Hydroxy-cyclohexyl-phenyl-ketone "Omnirad 184" from IGM Resins BV Heat curing agent: Covestro isocyanate Desmodur N-3300 Acrylic beads, particle size 5μm: Resin beads made from butyl methacrylate, Aica Kogyo Co., Ltd. "GB-05S" Silica particle size 2.2μm: Tosoh Silica "AZ-200" Urethane acrylic beads, particle size 17.5μm: Gifu Shellac Co., Ltd. "BJ-72" - Urethane beads, particle size 10μm: Negami Chemical Industries "C-600" - Urethane beads, particle size 32μm: Negami Chemical Industries "C-200"
[0066] (Examples and Comparative Examples: Manufacturing Method of Laminate) (Coating method) Each of the curable compositions obtained in the above Preparation Examples was coated on an easily-adhesive treated polyethylene terephthalate film (hereinafter, referred to as PET film, manufactured by Toyobo Co., Ltd., A4300, thickness 100 μm) by a bar coater coating method or a coating machine (gravure lithographic printing machine), to obtain a laminate having a resin layer of a thermosetting composition or an active energy ray-curable composition.
[0067] (Method of curing thermosetting composition) The laminates having the resin layers of the thermosetting compositions (Preparation Examples 1 to 3 and Preparation Examples H1 to H4) were heated in a thermostatic chamber at 40° C. for one day to be cured, thereby obtaining laminates of Examples 1 to 3 and Comparative Examples 1 to 4.
[0068] (Method of curing active energy ray-curable composition) A laminate having a resin layer of the active energy ray curable composition (Preparation Example 4: for UV curing, Preparation Example 5: for electron beam curing) was irradiated with UV rays or electron beams in an atmosphere with an oxygen concentration of less than 5%, to obtain laminates of Examples 4 to 5. The ultraviolet irradiation device used to cure the resin layer of the active energy ray curable composition of Preparation Example 4 was an ultraviolet irradiation device manufactured by GS Yuasa Corporation. The integrated light amount measuring device (illuminance meter) used was an ultraviolet integrated light amount meter "Industrial UV Checker UVR-N1" manufactured by GS Yuasa Corporation. As the electron beam irradiation device for curing the resin layer of the active energy ray curable composition of Preparation Example 5, "Electrocurtain EC250 / 15 / 180L" manufactured by Iwasaki Electric Co., Ltd. was used. The UV radiation dose is 56 mJ / cm 2 The electron beam irradiation dose was standardized to 50 kGy.
[0069] The obtained laminate and the resin beads used therein were measured and evaluated for the following measurement items.
[0070] (surface roughness measurement) The average roughness Ra (μm) and maximum height Rz (μm) of the resin layer surface of the laminate were measured using a contact type roughness meter (Tokyo Seimitsu Co., Ltd., SURFCOM NEX) in accordance with JIS B0601 and JIS B0633. The resin layer surface was scanned with a spherical indenter with a tip radius of 2 μm at a scanning speed of 0.06 mm / s, and Ra and Rz were obtained from a roughness curve using a reference length and low-pass cutoff length corresponding to the standard.
[0071] (Resin beads Young's modulus measurement) A nanoindenter (Elionix, ENT-2100) was used to evaluate in accordance with ISO 14577. Measurements were performed on the center of the resin bead observed in a microscopic image of the resin layer surface using a Berkovich indenter with an indentation load of 25 μN, an indentation time of 10 seconds, a creep time of 10 seconds, and an unloading time of 10 seconds, and the Young's modulus (MPa) of the resin bead was obtained from the unloading portion of the obtained load-displacement curve using the Oliver-Pharr method.
[0072] (Kinematic friction coefficient measurement) A tribometer (Tactile Force Plate TF-2020, sold by Tech Gihansha) was used to obtain the dynamic friction coefficient when touching the surface of the resin layer with the hand. The laminate was placed on the tribometer, and the dynamic friction coefficient was measured for 30 seconds while the palm of the dominant hand was traced over the surface of the resin layer while changing the speed and vertical load. During the 30-second measurement, the dynamic friction coefficients at a vertical load of 200g and a speed of 50mm / s were collected and averaged. The same experiment was also conducted on three men and three women in their 20s to 50s, and the average results of the dynamic friction coefficients of a total of six people were used.
[0073] (Evaluation of smoothness) Ten healthy subjects, five men and five women in their 20s to 50s, were asked to freely touch the resin layer surface of the laminate with the palm of their dominant hand and were asked to rate the smoothness on a seven-point scale from 1 to 7. Here, 7 points represents the sample that felt the smoothest, and 1 point represents the sample that felt the least smooth. The average value of the results of the 10 subjects was used. A score of less than 5 was considered a failure, and a score of 5 or more was considered a pass.
[0074] (Scratch resistance evaluation) The scratch resistance of the resin layer surface of the laminate was confirmed by rubbing 10 times with steel wool (#0000) under a load of 500 g using an abrasion tester (Rubbing Tester, Ohira Rika Kogyo Co., Ltd.). The condition of the coating surface after rubbing was scored according to the following three-level evaluation. ○: Almost no noticeable scratches. △: Scratches cover more than half of the surface. ×: The coating film peeled off.
[0075] (Evaluation of Adhesion) Cellotape (registered trademark) manufactured by Nichiban Co., Ltd. was applied to the surface of the resin layer of the laminate and rapidly peeled off in a 45° direction, and the peeling state of the resin layer was observed. The state of the resin layer surface after peeling was rated according to the following three-level evaluation. ○: More than 90% of the resin layer remains △: 50-90% of the resin layer remains ×: Less than 50% of the resin layer remains
[0076] The evaluation results of the Examples are shown in Table 1, and the evaluation results of the Comparative Examples are shown in Table 2. Moreover, blank spaces indicate that no compound was used.
[0077] [Table 1]
[0078] [Table 2]
[0079] In the examples, all of the evaluation items met the pass criteria, whereas in the comparative examples, none of the indicators were met.
Claims
1. A laminate having a substrate and a resin layer provided on the substrate, the resin layer satisfying (1) to (4). (1) The resin layer is a layer formed by forming a resin layer of a heat- or active energy ray-curable composition containing 1 to 50% by mass of 1 to 10 μm resin beads or 1 to 50% by mass of silica into a film by exposure to heat or active energy rays. (2) The coefficient of dynamic friction of the resin layer surface with the hand is 0.35 or less. (3) The average roughness Ra, which is a value representing the unevenness of the surface, is 3 μm or less, and the maximum height Rz is 20 μm or less. (4) The Young's modulus, which is a value of hardness of the resin beads of the laminate, is 1000 MPa or more.
2. The laminate according to claim 1, wherein the resin layer is a layer formed by thermally coating a resin layer of a thermosetting composition containing a polyol and an isocyanate, the polyol containing 1 to 50% by mass of 1 to 10 μm resin beads or 1 to 50% by mass of silica.
3. The laminate according to claim 1, wherein the resin layer is a layer formed by irradiating an active energy ray with a resin layer of an active energy ray-curable composition containing a (meth)acrylic monomer containing 1 to 50% by mass of 1 to 10 μm resin beads or 1 to 50% by mass of silica to form a film.
4. A heat- or active energy ray-curable coating agent containing 1 to 50 mass % of resin beads having an average particle size of 1 to 10 μm or 1 to 50 mass % of silica, wherein a layer formed by irradiation with heat or active energy rays satisfies (2) to (4). (2) The coefficient of dynamic friction of the resin layer surface with the hand is 0.35 or less. (3) The average roughness Ra, which is a value representing the unevenness of the surface, is 3 μm or less, and the maximum height Rz is 20 μm or less. (4) The Young's modulus, which is a value of hardness of the resin beads of the laminate, is 1000 MPa or more.
5. A decorative sheet using the laminate according to any one of claims 1 to 3.
Citation Information
Patent Citations
Decorative sheet
JP2021053996A
Decorative sheet, transfer sheet and decorative molding
JP2023010419A